Engineering of a genetic circuit with regulatable multistability. Issue 8 (24th July 2018) - Li, Tingting; Dong, Yiming; Zhang, Xuanqi; Ji, Xiangyu; Luo, Chunxiong; Lou, Chunbo; Zhang, Haoqian M.; Ouyang, Qi
Abstract : Synthetic biologists are dedicated to designing genetic systems from the bottom up to understand how living systems work. Abstract : Synthetic biologists are dedicated to designing genetic systems from the bottom up to understand how living systems work. To date, a variety of genetic circuits exhibiting bistability have been designed, greatly expanding our understanding of the biological multistability in natural systems. However, the study of more complex forms of biological multistability using synthetic methods is still limited. In this report, we describe the engineering of a genetic circuit with regulatable multistability. A novel genetic toggle switch exhibiting inducible bistability and a self-activation circuit were individually designed and characterized, after which they were assembled to create a circuit that presents tristability. In bacteria, this synthetic circuit enables cells to differentiate spontaneously into three different states of gene expression. Moreover, the multistability of the circuit can be modulated by external inputs. This work provides a synthetic biology framework for the study of biological multistability and may help to understand natural multistability phenomena.